Being known in undergraduate social work education: the role of instructors in fostering student engagement and motivation - Rodriguez-Keyes, Elizabeth; Schneider, Dana A; Keenan, Elizabeth King (Social Work Education, 2013)
Most undergraduate students pursue a social work major because of their desire to help others. Students tend to be more interested in doing than in understanding the research and knowledge of the profession and the complexities of social work practice. Instructors are often faced with the challenge of enhancing student motivation to learn challenging course material. This study explored student perceptions of instructor influences on their motivation and engagement in learning. Through online surveys, students described their experiences of being known and how those experiences affected their participation in practice, research, and human behavior in the social environment courses. Results showed that instructor caring (providing recognition, expressing relational qualities, and responding to students) positively influences student motivation and affective learning by increasing comfort, willingness to ask questions, take risks, and overall participation. Conversely, of those who reported mixed experiences or who felt unknown, most reported a negative impact on their motivation and participation. These findings suggest that social work faculty can influence student motivation and engagement with essential social work curriculum by expressing care and helping students feel known in the classroom. © 2013 Copyright Taylor and Francis Group, LLC.
16 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/006-141-699-158-36X tex.type: [object Object]
Keywords: BSW Education; Being Known; Instructor Influence; Motivation; Student Engagement; dept.swk